Oracle database 11g release 2 performance tuning tips & techniques - Niemiec, Richard J. (McGraw-Hill, 2012)
"Systematically identify and eliminate database performance problems with help from Oracle Certified Master, Richard Niemiec. Filled with real-world case studies and best practices, Oracle Database 11g Release 2 Performance Tuning Tips & Techniques details the latest monitoring, troubleshooting, and optimization methods. Find out how to find and fix bottlenecks, configure storage devices, execute effective queries, and develop bug-free SQL and PL/SQL code. Testing, reporting, and security enhancements are also covered in this Oracle Press guide"--Vydavatelská anotace
"Best practices for optimizing database performance"--Z obálky
Keywords: Oracle 11g (databázový systém); databázové systémy; správa databází; Oracle 11g; database management systems; database administration; příručky; handbooks, manuals, etc